Referendums around the world : the continued growth of direct democracy - Qvortrup, Matt.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Surveying all referendums around the world since 1793, Dr Qvortrup and contributors provide a thorough account of why and when citizens have been asked to vote on policy issues. Referendums Around the World is essential reading for political scientists and others interested in direct democracy as well as representative government.
Keywords: Science; Science; Science, general